한국 여성들의 wellness를 위한 스마트 리빙 - 김미정(Mi Jeong Kim); 조명은(Myung Eun Cho) (디지털콘텐츠학회논문지, 2020)
본 연구는 여성의 wellness를 중심현안으로 현재의 다양한 IT기술을 통해 여성을 위한 스마트 리빙 구현을 제시하고자 하였다. 조사대상자는 서울시에 거주하는 30~60세에 해당하는 여성들로 결혼여부와 자녀연령에 따라 미혼여성, 초등학령기 자녀를 둔 기혼 여성, 성인 자녀를 둔 기혼 여성의 세 개의 집단으로 층화표집(stratified sampling)을 하였다. 각 그룹별로 50부씩 총 150부를 분석에 활용하였다. 연구 결과는 다음과 같다. wellness 모델을 통해 다차원적 측면에서 분석한 결과 혼인과 자녀 유무에 따라 여성들의 생활과 태도는 매우 달랐다. 조사대상 여성들은 생활 속에 새롭게 등장하고 있는 혁신적인 정보 기술에 대한 개념과 이해가 부족하였으며, 여성 그룹들 간의 기술 활용성, 기술 인식, 기술 역할, 기술 필요도 등에는 차이가 있었다. 분석 결과를 토대로 한국 여성들의 wellness를 지원하는 스마트 리빙을 여성 유형에 맞게 제안하였다. The purpose of this study is to suggest the implementation of smart living for women through various IT technologies. The subjects were women aged 30-60 years old who lived in Seoul and we conducted stratified sampling in three groups according to marital status and child age: single women, married women with elementary school children, and married women with adult children. A total of 150 copies, 50 copies for each group, were used for the analysis. As a result of multidimensional analysis through wellness model, women's life and attitudes were very different according to marriage and parental status. The women surveyed lacked the concept and understanding of innovative information technology emerging in their daily lives, and there was a difference in the degree of utilization, awareness, role, and needs of technology among women groups. Based on the results, we proposed a smart living direction that supports the wellness of Korean women according to the type of women. KCI Citation Count: 0